Upaya Guru Pendidikan Agama Islam dalam Meimplementasikan Kurikulum Merdeka di Madrasah Aliyah Al Falah Puteri - Zahratul Muna (Fakultas Agama Islam Universitas Billfath, 2024)
This research aims to find out the problems faced by teachers when implementing the merdeka curriculum and the solutions made by PAI teachers and the school in dealing with the problems faced when implementing the merdeka curriculum at MA Al Falah Puteri, written using a qualitative approach. The data collection technique used was observation, interviews, and documentation using qualitative data analysis consisting of three stages, namely the data reduction stage, data display, and conclusion or verification. The results found problems faced by teachers when implementing the merdeka curriculum which has only been running for one semester, starting from PAI teachers' lack of understanding of the merdeka curriculum, lack of references, use of information technology media which has not been maximized, and not being able to maximize the existing time allocation using the appropriate methods. involves student activity, teachers are not yet fully accustomed to being facilitators, on the other hand students are also not accustomed to being active in class, students' self-awareness to participate in class is still low, their interest in learning is also still low. The school and teachers have made efforts to solve the problem and slowly the problem has begun to be resolved, but learning using the merdeka curriculum is not optimal because it is still in the adjustment stage.